Enhanced Antitumor Activity of Lidocaine Nanoparticles Encapsulated by a Self-Assembling Peptide - Yang, Yang; Sun, Jiaxiao; Peng, Fei; Liu, Haibei; Zhao, Guoyan; Chen, Junjie; Zhang, Wensheng; Qiu, Feng (Frontiers in Pharmacology, 2022)
Although traditional local anesthetics (LAs) such as lidocaine have been commonly used for sensor blocking and pain relief, their potential antitumor activity has also attracted considerable attention in recent years. However, since nearly all LAs are used as small molecule compounds with high water-solubility, their antitumor activity is limited by poor cellular uptake and fast in vivo clearance. Regarding this problem, fabricating LA nanoparticles might be a simple strategy to improve their antitumor activity. In this study, lidocaine nanoparticles (LNPs) were prepared by using a self-assembling peptide to encapsulate a water-insoluble lidocaine base (LB). TEM and DLS showed that the peptide could encapsulate LB and form stable nanoparticles with an average size of less than 100 nm. Compared with soluble lidocaine hydrochloride, the LNPs could inhibit the proliferation and migration of A375 cells more efficiently. As tested in nude mice models, LNPs could suppress the development of tumors more effectively. These results indicated that using self-assembling peptide as the carrier, LNPs could be facilely obtained, which could be used as promising dual-functional drugs with both antitumor and anesthesia activity.